2017
DOI: 10.1155/2017/5216562
|View full text |Cite
|
Sign up to set email alerts
|

Smoking, Gender, and Overweight Are Important Influencing Factors on Monocytic HLA-DR before and after Major Cancer Surgery

Abstract: Background Monocytic human leukocyte antigen D related (mHLA-DR) is essential for antigen-presentation. Downregulation of mHLA-DR emerged as a general biomarker of impaired immunity seen in patients with sepsis and pneumonia and after major surgery. Influencing factors of mHLA-DR such as age, overweight, diabetes, smoking, and gender remain unclear. Methods We analyzed 20 patients after esophageal or pancreatic resection of a prospective, randomized, placebo-controlled, double-blind trial (placebo group). mHLA… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 58 publications
1
6
0
Order By: Relevance
“…The result of the present study corresponded with the earlier studies, which reported that overweight or obese patients have an increased risk of POP [1517]. Obese patients often have reduced lung volume, altered ventilation pattern, decreased immune function, and comorbid conditions, which are risk factors for intra- and postoperative complications [1618]. Overweight and obesity are spreading worldwide, and thoracic surgeons will encounter more overweight patients in need of surgery in the future [19].…”
Section: Discussionsupporting
confidence: 90%
“…The result of the present study corresponded with the earlier studies, which reported that overweight or obese patients have an increased risk of POP [1517]. Obese patients often have reduced lung volume, altered ventilation pattern, decreased immune function, and comorbid conditions, which are risk factors for intra- and postoperative complications [1618]. Overweight and obesity are spreading worldwide, and thoracic surgeons will encounter more overweight patients in need of surgery in the future [19].…”
Section: Discussionsupporting
confidence: 90%
“…Although not routinely incorporated in current sepsis care guidelines despite existence of functional cellular markers (13)(14)(15), the detection of an acquired immunosuppression syndrome (AIS) seems to be essential to tailor the immune therapy (16). Reduced mHLA-DR expression impairs the T-cells activation, which increases the likelihood of secondary infections by five times and is per-se associated with endotoxin tolerance (17,18). Measurements beginning on day 17 of the illness revealed that merely 22% to 28% of CD14+ monocytes expressed HLA-DR.…”
Section: Discussionmentioning
confidence: 99%
“…Obese patients often have reduced lung volume, altered ventilation pattern, and comorbid conditions, which are risk factors for intra-and postoperative complications 13,14. Being overweight is an important influencing factor on pre- and postoperative immune function 15. Additionally, an elevated BMI in patients will lead to increased difficulty during surgery and prolonged operative times 16.…”
Section: Discussionmentioning
confidence: 99%